A Rose from Two Gardens - Brennan, Marcia (University of California Health Humanities Press, 2024)
Intriguing parallels arise between contemporary end of life images and themes expressed historically in the writings of Thérèse of Lisieux, the Catholic saint who is known as the “Little Flower.” Drawing on her combined experiences as a professor of the humanities at Rice University, and as an Artist In Residence in Palliative, Rehabilitation, and Integrative Medicine at the M.D. Anderson Cancer Center, the author examines topics such as the paradoxical grandeur of small things, the spiritual significance of flowers, compassion and consolation in the wake of human suffering, the power of mystical dreams and prophetic visions, and vibrant conceptions of eternal life. Ultimately, Saint Thérèse’s “little way” and contemporary end of life imagery emphasize the knowledge of the heart, which teaches how to see the hidden in everyday life, and how to recognize the dedication of love.